MBRS-37. IN VITRO MODELLING OF TUMOUR EVOLUTION AND RADIOTHERAPY RESISTANCE IN MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Richardson, Stacey; Hill, Rebecca; Selby, Matthew; Lindsey, Janet; Rafiee, Gholamreza; Bailey, Simon; Williamson, Daniel; Clifford, Steve
Abstract: Medulloblastoma relapse occurs in 30-40% of patients, is almost universally fatal and accounts for 10% of childhood cancer deaths. Acquisition of combined MYC/MYCN and TP53 defects occurs in 30% of recurrences following standard-upfront-treatment. Therapy-related selection pressure plays a role in the emergence of treatment resistant clones. We hypothesised that in medulloblastoma, radiotherapy provides this pressure, resulting in the converging evolution witnessed at relapse. Modelling this process of selection, provides the opportunity to identify mechanisms of treatment resistance. To investigate this hypothesis, we developed novel in vitro models of radiotherapy resistance. Using two SHH subgroup medulloblastoma cell lines (UW228-2/ONS76) we delivered a radiotherapy regimen in vitro which mimicked that delivered to patients (54Gy administered 5 days/week in 1.8Gy daily fractions). Radiation treatment induced massive cell death, however in all replicates (n=4) a small population of senescent cells remained after treatment. This phenotype persisted for 4-10 weeks, before colonies of surviving cells exited senescence and entered proliferation, mimicking what we hypothesise occurs in the relapsed human disease. Importantly, whole-exome-sequencing of both cell lines revealed an emergence of predicted deleterious variants post-therapy, compared with untreated counterparts. Cross-refencing to human disease identified 22 gene defects (e.g. NOTCH4 and GLI1) emerging in our models which were also detected in biopsies of relapsed human tumours. Our novel in vitro model faithfully recapitulates human disease behaviour and implicates candidate genes in common with human recurrent tumours. This approach provides significant opportunities to understand the biological mechanisms of radiotherapy-related resistance and identify novel therapeutic targets in relapsed medulloblastoma.